Prevalence and susceptibility profile to antibacterial drugs of diarrheagenic Escherichia coli isolated from children with acute intestinal infection - M. Lusta; O. Voronkova; T. Shevchenko; V. Chornyi; I. Yesaulenko; A. Breus; Y. Maistrenko A. Kovalenko; T. Ponomarova-Herasymiuk (Regulatory Mechanisms in Biosystems, 2025)
Escherichia coli is a common inhabitant of the gastrointestinal tract of humans and warm-blooded animals, often ass o ciated with diarrhea. Different pathotypes can be distinguished for this bacterium, depending on virulence factors and the disease it causes. To isolate and identify E. coli , stool samples were transferred to Endo medium, and the cultures were inc u bated at 37 ± 1 C for 18 – 24 hours under aerobic conditions. Lactose-positive and lactose-negative colonies were subcultured onto Olkenytskyi medium (trisaccharide agar) for primary biochemical identification and slant and meat-peptone agar for accumulation of pure culture . T he cultures were incubated at a temperature of 37 ± 1 C for 18 – 24 hours under aerobic cond i tions. Suspected E. coli cultures were subjected to serotyping in agglutination reaction on a glass of pure culture with polyv a lent and monovalent sera. The sensitivity of pathogenic E. coli of a certain serotype to antibacterial drugs was determined by the disk diffusion method in accordance with the requirements of the recommendations of the European Committee on Ant i microbial Susceptibility Testing. In 2022 – 2024, 3,484 stool samples from children with acute intestinal infection who were inpatients at the Municipal Non - C ommercial Enterprise “ City Clinical Hospital No. 6 ” of the Dnipro City Council were e x amined. 202 cultures of pathogenic E. coli strains were isolated, the overall efficiency (seeding rate) was 5.8%. It was found that the highest research effectiveness in 2022 was observed in the winter period of the year, in 2023 – in the summer-autumn period, and in 2024 – in the summer period. The specific gravity of isolated pathogenic E. coli strains among boys and girls with acute intestinal infection during the studied period wa s stable and amount ed to 58.9% for boys and 41.1% for girls. For the period 2022 – 2024, among the isolated pathogenic E. coli strains, the most frequently encountered strains were serotype O 18 – 14.4%, serotype O 44 – 18.8%, serotype O 78 – 7.4%, serotype O 145 – 5.4%, serotype O 26 – 5.0%, serotype O 103 – 5.0%. The overall susceptibility profile to antibacterial drugs of pathogenic E. coli strains isolated from the stool samples of children with acute intestinal infection in 2022-2024 was 54.5% for ampicillin, 49.0% for amoxicillin-clavulanic acid, 91.6% for ceftriaxone, 96.9% for ceftazidime, 97.9% for cefepime, 89.1% for cefoxitin (screening), and 93.6% for ciprofloxacin. The aim of the study was to determine the prevalence of pathogenic E. coli serotypes and the antibacterial drug sensitivity profile of the isolated strains among children with acute intestinal infection.